Белоснежка и король грозовая туча - Прокофьева Софья Леонидовна (Белоснежка, 2004)
Экземпляры: Д.О. (20201012) / Инвентарный номер: 40217 / Цена: 48.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: П 80 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6